The Impact of CSR on Consumers Purchase Intention: The Mediating Role of Corporate Reputation and Moderating Peers Pressure - Qasim, Saba; Siam, Mohammad R.A; Sallaeh, Salniza Bt Md (International Journal of Supply Chain Management, 2017)
This study examines the link between corporate social responsibility and consumer purchase intention by focusing on the mediating role of corporate reputation and the moderating role of peer pressure. The results of distinctive data from 378 consumers of Pakistan reveal that corporate reputation positively relates to consumer purchase intention, and that corporate reputation fully mediates the positive influence of corporate social responsibility on consumer purchase intention. We also found that peer pressure moderates the relationship between the corporate reputation and consumer purchase intention. Furthermore, the mediating effect between corporate reputation and consumer purchase intention is moderated by peer pressure, that is to say moderated mediation. We discuss implications of these findings for research and practice.